Anthracoidea transberingiana, a new smut species on Carex pauciflora from Beringia - Piątek, Marcin (Phytotaxa, 2014)
The new smut fungus, Anthracoidea transberingiana attacking ovaries of Carex pauciflora, is described and illustrated from Beringia (Alaska and Kamchatka). The new species is compared with Anthracoidea caricis-pauciflorae infecting the same host plant species predominantly in northern Europe, from which it differs in having smaller spores, thinner spore walls, 2–3 weakly visible internal swellings and somewhat less prominent spore ornamentation.